Abnormal bone marrow microenvironment: the "harbor" of acute lymphoblastic leukemia cells. Issue 2 (April 2021) - Chen, Zehui; Zheng, Yaxin; Yang, Yaling; Kang, Junnan; You, M. James; Tian, Chen
Abstract : Abstract: Bone marrow (BM) microenvironment regulates and supports the production of blood cells which are necessary to maintain homeostasis. In analogy to normal hematopoiesis, leukemogenesis is originated from leukemic stem cells (LSCs) which gives rise to more differentiated malignant cells. Leukemia cells occupy BM niches and reconstruct them to support leukemogenesis. The abnormal BM niches are the main sanctuary of LSCs where they can evade chemotherapy-induced death and acquire drug resistance. In this review, we focus on the protective effects of BM niche cells on acute lymphoblastic leukemia cells.